Habilidades metacognitivas de los estudiantes de primer semestre de la facultad de educación en la UAN - Beltrán Cristancho, Jorge Alexander (Universidad Antonio Nariño, 2023)
Among the latest strategies for acquiring new knowledge, is metacognition, which is addressed in this paper to have a clear idea about the development of metacognitive skills in 2015-1 students of the Faculty of Education UAN on the subject: Foundations of Education, in which the proposed by Flavell (1970) model, one of the main forerunners, who defines metacognition as "thought processes of people on their own knowledge and understanding was evident they have about their own cognitive action. "